Human coronavirus dependency on host heat shock protein 90 reveals an antiviral target. Issue 1 (1st January 2020) - Li, Cun; Chu, Hin; Liu, Xiaojuan; Chiu, Man Chun; Zhao, Xiaoyu; Wang, Dong; Wei, Yuxuan; Hou, Yuxin; Shuai, Huiping; Cai, Jianpiao; Chan, Jasper Fuk-Woo; Zhou, Jie; et al.
ABSTRACT: Rapid accumulation of viral proteins in host cells render viruses highly dependent on cellular chaperones including heat shock protein 90 (Hsp90). Three highly pathogenic human coronaviruses, including MERS-CoV, SARS-CoV and SARS-CoV-2, have emerged in the past 2 decades. However, there is no approved antiviral agent against these coronaviruses. We inspected the role of Hsp90 for coronavirus propagation. First, an Hsp90 inhibitor, 17-AAG, significantly suppressed MERS-CoV propagation in cell lines and physiological-relevant human intestinal organoids. Second, siRNA depletion of Hsp90β, but not Hsp90α, significantly restricted MERS-CoV replication and abolished virus spread. Third, Hsp90β interaction with MERS-CoV nucleoprotein (NP) was revealed in a co-immunoprecipitation assay. Hsp90β is required to maintain NP stability. Fourth, 17-AAG substantially inhibited the propagation of SARS-CoV and SARS-CoV-2. Collectively, Hsp90 is a host dependency factor for human coronavirus MERS-CoV, SARS-CoV and SARS-COV-2. Hsp90 inhibitors can be repurposed as a potent and broad-spectrum antiviral against human coronaviruses.